Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor exerts greater efficacy than atorvastatin on improvement of brain function and cognition in obese rats - Busarin Arunsak (2020)
© 2020 Elsevier Inc. The accumulation of lipid as a result of long-term consumption of a high-fat diet (HFD) may lead to metabolic and brain dysfunction. Atorvastatin, a recommended first-line lipid-lowering agent, has shown beneficial effects on metabolic and brain functions in several models. Recently, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor was approved as an effective therapeutic drug for dyslipidemia patients. However, few studies have reported on the effect of this PCSK9 inhibitor on brain function. In addition, the comparative efficacy on the improvement of metabolic and brain functions between PCSK9 inhibitor and atorvastatin in obese models have not been elucidated. We hypothesized that PCSK9 inhibitor improves metabolic and brain functions in an obese model to a greater extent than atorvastatin. Thirty-two female rats were fed with either a normal diet (ND) or HFD for 15 weeks. At week 13, ND rats were given normal saline and HFD rats were given either normal saline, atorvastatin (40 mg/kg/day) or PCSK9 inhibitor (4 mg/kg/day) for 3 weeks. Oxidative stress, blood brain barrier breakdown, microglial hyperactivity, synaptic dysplasticity, apoptosis, amyloid proteins production in the hippocampus and cognitive decline were found in HFD-fed rats. Atorvastatin and PCSK9 inhibitor therapies equally attenuated hippocampal apoptosis and amyloid protein production in HFD-fed rats. Interestingly, PCSK9 inhibitor had the greater efficacy than atorvastatin on the amelioration of hippocampal oxidative stress, blood brain barrier breakdown, microglial hyperactivity, synaptic dysplasticity in the hippocampus and cognitive decline. These findings suggest that PCSK9 inhibitor may be another drug of choice for improving brain function in the obese condition with discontinued statin therapy.